THE EFFECTIVENESS OF PHYSICAL SEPARATION PROCESS FOR THE ALLUVIAL TIN (HEINDA) ORE, MYANMAR - Win, Nay Zaw Htay; Numprasanthai, Apisit; Laowattanabandit, Pipat (MATTER: International Journal of Science and Technology, 2020)
Mineral beneficiation is a process by which valuable constituents of an ore are concentrated through a physical separation process. In the present investigation, tin ore samples were collected from the Heinda tin mine, Thanintharyi region, Myanmar. Heinda mine is tin placer deposits which are located about 50 Km east of Dawai, Tanintharyi, Myanmar. The mine can be reached by road from Poo Nam Ron checkpoint, Kanchanaburi Province, Thailand. In this study, particle size analysis (PSD) was carried out over the range of - 6.7 mm and +0.075 mm in 9 different mesh sizes. The operating variables used to determine the recovery effectiveness of the jigging and shaking table include; particle size, stroke, table slope, and dilution ratio, then the percent recovery of tin concentrate was evaluated by applying X-ray fluorescence (XRF). The results showed that the tin mineral concentrate of the jig separator is 70.7% and the shaking table is 49.8%. The cassiterite recovery processes were conducted by using physical separation processes and the discounted cash flow model (DCF) for an economic analysis of the project. In this study, the internal rate of return (IRR) is 11.45percent which is higher than the discount rate of 8 percent, and NPV is 790,886,832.61 US $. The payback period of the project is equal to 8 to 9 years of project life for 30 years. Consequently, the Heinda tin ore project is proven feasible.